2016
DOI: 10.1681/asn.2015111285
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Dysbiosis, Barrier Dysfunction, and Bacterial Translocation Account for CKD–Related Systemic Inflammation

Abstract: CKD associates with systemic inflammation, but the underlying cause is unknown. Here, we investigated the involvement of intestinal microbiota. We report that collagen type 4 α3-deficient mice with Alport syndrome-related progressive CKD displayed systemic inflammation, including increased plasma levels of pentraxin-2 and activated antigen-presenting cells, CD4 and CD8 T cells, and Th17- or IFNγ-producing T cells in the spleen as well as regulatory T cell suppression. CKD-related systemic inflammation in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
138
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(145 citation statements)
references
References 35 publications
2
138
0
5
Order By: Relevance
“…Once in circulation, in addition to inducing a general systemic inflammation [56] , these toxins are capable of mediating renal tubulointerstitial fibrosis via upregulation and activation of tumor necrosis factor-β1 and the renin-angiotensin-aldosterone system, contributing to epithelial-mesangial transformation and CKD progression [57][58][59] . This concept was nicely demonstrated recently by Andersen et al [60] . Using an Alport syndrome ( Col4α3 deficient)-CKD mouse model, the authors have demonstrated gut dysbiosis as a dominant source of systemic inflammation, including activation of innate and adaptive immune cells.…”
Section: Gut Factorsmentioning
confidence: 57%
“…Once in circulation, in addition to inducing a general systemic inflammation [56] , these toxins are capable of mediating renal tubulointerstitial fibrosis via upregulation and activation of tumor necrosis factor-β1 and the renin-angiotensin-aldosterone system, contributing to epithelial-mesangial transformation and CKD progression [57][58][59] . This concept was nicely demonstrated recently by Andersen et al [60] . Using an Alport syndrome ( Col4α3 deficient)-CKD mouse model, the authors have demonstrated gut dysbiosis as a dominant source of systemic inflammation, including activation of innate and adaptive immune cells.…”
Section: Gut Factorsmentioning
confidence: 57%
“…Noteworthy and opposite to findings in the Chinese patient cohort, they observed a higher amount of colony forming units per gram of feces. Again, they observed differentially structured communities, with changes in the class of Bacteroidales, Burholderiales (family of Alcaligenaceae), Enterobacteriales, and Verrucomicrobiales [9]. In aggregate, these studies show that ESRD promotes alterations in the composition of the gut microbiota.…”
Section: Gut Microbiota In Ckdmentioning
confidence: 80%
“…Whether CKD, similar to dietary changes [29] may cause alterations of the inner colonic mucus layer, thereby compromising the gut barrier function, remains to be studied. Uremic serum and plasma increased intestinal permeability in vitro, suggesting the involvement of a humoral component [30,9]. Both direct toxicity by uremic retention molecules (especially ammoniumhydroxide) and butyrate depletion may be involved.…”
Section: Intestinal Barrier In Ckdmentioning
confidence: 96%
See 1 more Smart Citation
“…The eradication of facultative anaerobic microbiota with antibiotics in uremic rats prevented bacterial translocation and reduced serum endotoxin levels and markers of systemic inflammation [121]. Thus, the gut seems to be a source of inflammation in CKD.…”
Section: Gut Ecosystem In Ckd and Immunitymentioning
confidence: 97%